Socialization and Training of 'Kids' Athletics' for Physical Education Teachers and Elementary School Students as an Effort to Disseminate Play-Based Sports Learning - Galih Farhanto; Edi Irwanto; Donny Setiawan; Puji Setyaningsih; Ach. Zayul Mustain; Danang Ari Santoso; Arya T Candra (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The low interest of elementary school students in athletics is caused by conventional teaching methods and limited facilities. This community service program aims to socialize and train teachers on implementing circuit-based Kids' Athletics for PE teachers and students in partner public elementary schools. The method relies on Technology Transfer and Participatory Assistance approaches, consisting of policy socialization, technical workshops on self-modifying equipment assembly, and direct on-field coaching clinics. Evaluation results indicate a significant increase in teachers' cognitive competence, with the average score rising from an initial 58.3% to 89.7% post-training. Psychomotorically, teachers successfully assembled and managed four circuit game stations (Formula One, Shuttle Hurdle, Frog Jump, Turbo Throwing) safely. Students' psychological responses after the intervention also showed highly increased interest in athletics, reaching 86.5% (exceeding the initial target of ≥ 80%). The program concluded with the donation of eco-friendly modified athletic equipment packages and printed modules to ensure independent program sustainability. In conclusion, this synergy of socialization and training effectively overcomes physical infrastructure barriers while enhancing joyful and inclusive PE instruction